2017
DOI: 10.1177/0306624x17712966
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences of Violent Female Offenders: A Comparison of Homicide and Sexual Perpetrators

Abstract: Adverse childhood experiences are associated with a multitude of health and social problems. In addition to an increased risk of poor health, mental disorders, and substance abuse, childhood maltreatment is also significantly related to adult violent offending. Although gender-specific analyses suggest that early childhood maltreatment precedes later violence for males across offense categories, it is unknown whether this association also applies to different types of female offenders. This study explores the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 42 publications
3
8
0
1
Order By: Relevance
“…For example, for obvious reasons, studies on intimate partner homicide (15, 16) have a higher prevalence of offenders within intimate partner relations/marriage. Further, there was also a high prevalence of adverse childhood experience and lifetime victimization within the total sample of female offenders, which likewise is consistent with prior research (20,26,27,29,31). In conclusion, regarding background factors, the results in the present study were in line with previous studies, and also merge previous disparate results.…”
Section: Background and Demographicssupporting
confidence: 93%
“…For example, for obvious reasons, studies on intimate partner homicide (15, 16) have a higher prevalence of offenders within intimate partner relations/marriage. Further, there was also a high prevalence of adverse childhood experience and lifetime victimization within the total sample of female offenders, which likewise is consistent with prior research (20,26,27,29,31). In conclusion, regarding background factors, the results in the present study were in line with previous studies, and also merge previous disparate results.…”
Section: Background and Demographicssupporting
confidence: 93%
“…In this study, we focus on murderous behaviors that involve some degree of premeditation and intention. However, the causes of murderous behaviors are complicated and include psychosocial and precipitating stressors (Marono et al, 2020); several studies have reported that adverse childhood experiences are associated with the risk of violent behavior and delinquency (DeLisi & Beauregard, 2018; Pflugradt et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although the existing body of research suggests that child maltreatment and psychopathology play a role in female violent offending, there are a number of limitations that detract from our ability to draw firm conclusions. First, the majority of studies have been cross-sectional, relying heavily on retrospective self-reports of childhood victimization (Browne et al 1999;Harlow 1999;Lynch et al 2012;McClellan et al 1997;Pflugradt et al 2017;Zlotnick 1997), which is potentially problematic because of problems with forgetting, reconstruction of memory, and inconsistencies in reports over time (Brewin et al 1993;Henry et al 1994;Offer et al 2000;Schraedley et al 2002). Second, many studies (e.g., Ogloff et al 2012;Papalia et al 2017;Siegel and Williams, 2003;Trabold et al 2015) have focused on only one type of abuse (sexual), rather than multiple types.…”
Section: Introductionmentioning
confidence: 99%